SLANG IN AREAS OF EVERYDAY LIFE IN A MOVIE ENTITLED 8 MILE - Fanani, Faiz Iqbal (UNIVERSITAS SLAMET RIYADI, 2017)
ABSTRACTSlang is a part of sociolinguistic and slang it self elaborated in a social life of human being. Slang ussualy used by a person or a group in dialy life to interact each other. As a person who learn English, word of slang may hard to understand by a non native speakers. Movie with English language where ussualy have content of sociolinguistic like a slang phenomena. Hence, the aims of this research to find out the kind of slang in areas in everyday life in 8 Mile movie.This research was conducted and the method of the research study used qualitative method. The data was collected through watch the movie, read the script of the movie, determining the character which will be analyzed, making notes for aspect in slang language elaborated by some events eses by main character which contained in the movie, classifying the aspects in slang language elaborated by some events and effects related slang language uses by major character which contained in the movie.The results of the research showed the kind of slang in 8 Mile movie such as insult, the human body, sex, work, euphemisms, relationships, and unemployment slang. The result of each slang is insult slang 16 words, relationships slang 6 words, the human body 1 word, euphemisms 2 words, unemployment 1 words, sex 3 words and work slang 1 words the total of the slang was Jimmy utered in 8 Mile movie is 30 words. Key words: Slang; 8 Mile movie, Qualitative method, Sociolinguistic study, Slang in 8 Mile movie, Slang in area of everyday life ABSTRAKBahasa gaul adalah bagian dari sosiolinguistik dan bahasa gaul itu dielaborasi dalam kehidupan sosial manusia. Slang biasanya digunakan oleh seseorang atau kelompok dalam kehidupan dialy untuk berinteraksi satu sama lain. Sebagai orang yang belajar bahasa Inggris, kata slang mungkin sulit dimengerti oleh penutur asli. Film dengan bahasa Inggris dimana biasanya memiliki konten sosiolinguistik seperti fenomena gaul. Oleh karena itu, penelitian ini bertujuan untuk mengetahui jenis bahasa gaul dalam kehidupan sehari-hari dalam film 8 Mile. Penelitian ini dilakukan dan metode penelitian yang digunakan adalah metode kualitatif. Data dikumpulkan melalui menonton film, membaca skrip film, menentukan karakter yang akan dianalisis, membuat catatan untuk aspek dalam bahasa gaul yang diuraikan oleh beberapa peristiwa oleh karakter utama yang terkandung dalam film, mengklasifikasikan aspek dalam bahasa gaul bahasa yang dielaborasi oleh beberapa peristiwa dan efek terkait bahasa slang digunakan oleh karakter utama yang terkandung dalam film tersebut. Hasil penelitian menunjukkan jenis slang dalam film 8 Mile seperti penghinaan, tubuh manusia, seks, pekerjaan, eufemisme, hubungan, dan gaul pengangguran. Hasil dari setiap gaul adalah penghinaan gaul 16 kata, hubungan gaul 6 kata, tubuh manusia 1 kata, eufemisme 2 kata, pengangguran 1 kata, seks 3 kata dan kerja gaul 1 kata total gaul yang diucapkan Jimmy dalam film 8 Mile adalah 30 kata. Kata kunci: Slang; Film 8 Mile, Metode Kualitatif, Studi Sosiolinguistik, Slang in 8 Mile film, Slang di bidang kehidupan sehari-hari